2023
DOI: 10.4236/ojss.2023.135010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Agent Purple, Agent Orange and Agent Blue on Royal Thai Air Force Base Perimeters in Thailand during the Vietnam War

Abstract: Seven Royal Thai Air Force bases in Thailand were used by the United States Air Force (USAF) during the Vietnam War as staging hubs for operations in Laos and Cambodia. Five bases in Thailand, including Nakhon Phanom (NKP), Ubon, Korat, U-Tapao and Udorn endured sniper fire interdiction, perimeter penetration, and sapper (combat engineer) attacks. Nam Phong, an eighth Royal Thai Air Force base was used by the United States Marine Corps air operations starting in 1972. US Military personnel stationed throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, it also affects some of the Americans who served in Cambodia and Laos [12]. The VA, seemingly based on this limited recognition of Agent Orange's presence in Laos and Cambodia, does not extend the "automatic presumption of dioxin exposure" to the Americans who served in Cambodia and Laos but did not enter Vietnam [12]. A VA spokesperson, confirmed that the "automatic presumption of exposure" extends only to veterans who served in Vietnam.…”
Section: Veteran Affairs Benefits For Dioxin Affected American Veteransmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it also affects some of the Americans who served in Cambodia and Laos [12]. The VA, seemingly based on this limited recognition of Agent Orange's presence in Laos and Cambodia, does not extend the "automatic presumption of dioxin exposure" to the Americans who served in Cambodia and Laos but did not enter Vietnam [12]. A VA spokesperson, confirmed that the "automatic presumption of exposure" extends only to veterans who served in Vietnam.…”
Section: Veteran Affairs Benefits For Dioxin Affected American Veteransmentioning
confidence: 99%
“…Ranch Hand aircraft utilized bases in Thailand throughout the Vietnam War (Figure 6). Operation Ranch Hand used UC-123s that were launched from airbases in Thailand including Ubon, NKP, Udorn, and Takhli on numerous occasions to conduct missions against targets in Laos, Cambodia and Vietnam [12].…”
Section: Use Of Thailand Air Force Bases To Spray and Bomb The Ho Chi...mentioning
confidence: 99%
See 3 more Smart Citations